Detection of land use change using the R program (A case study of Phuket Island, Thailand) - Thinnukool,O. (Medwell Publishing, 2015)
Urban growth is an important topic that developers around the world need to assess because of expansion of the city which directly affects adjacent areas. After landreform was initiated in 1987 by Remote Sensing data (RS), developers became aware of the study of land planning and land policy. Although, Geographic Informahon System (GIS) Software can be used in detecting land use change, there is the need to pay the license cost. Nowadays, geographers have been able develop GIS Programs such as Map Windows GIS and Quantum GIS for detecting land use change. However, some techniques are not available with the free software. The main purpose for investigating land use change was to show loss and gain in areas and also to show the basic statistics. This study examines the use of GIS in land use change mapping for Phuket Island from 1967 to 2009. Secondary data from the Thai Department of Land Development was appropriate for analyzing land use change. Researchers used the data from supervised classifications to classify the RS data. For the analysis of land use categories change, the digitization approach was used. The computation was based on the actual number of observations for land use data on Phuket by free software, the R Program. Three categories of land use change were investigated: forest, agriculture and urban; quantitative analysis changed using a bubble plot matrix. The study illustrated the increasing trend of urban growth in tourist areas which directly affect the forest area on Phuket Island. Land use changes from one category to another have been clearly represented by map format using a scale of 1:1000. © Medwell Journals, 2014.